Does United Kingdom parliamentary attention follow social media posts? - John Bollenbacher; Niklas Loynes; John Bryden (EPJ Data Science, 2022)
Abstract News and social media play an important role in public political discourse. It is not clear what quantifiable relationships public discussions of politics have with official discourse within legislative bodies. In this study we present an analysis of how language used by Members of Parliament (MPs) in the United Kingdom (UK) changes after social media posts and online reactions to those posts. We consider three domains: news articles posted on Facebook in the UK, speeches in the questions-debates in the UK House of Commons, and Tweets by UK MPs. Our method works by quantifying how the words used in one domain become more common in another domain after an event such as a social media post. Our results show that words used in one domain later appear more commonly in other domains. For instance after each article on Facebook, we estimate that on average 4 in 100,000 words in Commons speeches had changed, becoming more similar to the language in the article. We also find that the extent of this language change positively correlates with the number of comments and emotional interactions on Facebook. The observed language change differs between political parties; in particular, changes in word use by Labour MPs are more strongly related to social media content than that of Conservative MPs. We argue that the magnitude of this word flow is quite substantial given the large volume of news articles shared on Facebook. Our method and results quantify how parliamentary attention follows public interest as expressed on Facebook and also indicate how this effect may be stronger for posts which evoke reactions on Facebook associated with laughter or anger.